HvWRKY2 acts as an immunity suppressor and targets HvCEBiP to regulate powdery mildew resistance in barley - Deshui Yu; Renchun Fan; Ling Zhang; Pengya Xue; Libing Liao; Meizhen Hu; Yanjun Cheng; Jine Li; Ting Qi; Shaojuan Jing; Qiuyun Wang; Arvind Bhatt; et al. (Crop Journal, 2023)
Plants use a sophisticated immune system to perceive pathogen infection and activate immune responses in a tightly controlled manner. In barley, HvWRKY2 acts as a repressor in barley disease resistance to the powdery mildew fungus, Blumeria graminis f. sp. hordei (Bgh). However, the molecular features of HvWRKY2 in its DNA-binding and repressor functions, as well as its target genes, are uncharacterized. We show that the W-box binding of HvWRKY2 requires an intact WRKY domain and an upstream sequence of ∼75 amino acids, and the HvWRKY2 W-box binding activity is linked to its repressor function in disease resistance. Chromatin immunoprecipitation (ChIP)-seq analysis identified HvCEBiP, a putative chitin receptor gene, as a target gene of HvWRKY2 in overexpressing transgenic barley plants. ChIP-qPCR and Electrophoretic Mobility Shift Assay (EMSA) verified the direct binding of HvWRKY2 to a W-box-containing sequence in the HvCEBiP promoter. HvCEBiP positively regulates resistance against Bgh in barley. Our findings suggest that HvWRKY2 represses barley basal immunity by directly targeting pathogen-associated molecular pattern (PAMP) recognition receptor genes, suggesting that HvCEBiP and likely chitin signaling function in barley PAMP-triggered immune responses to Bgh infection.